2018
DOI: 10.1016/j.jiph.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes toward HIV/AIDS among the general population of Jeddah, Saudi Arabia

Abstract: Knowledge gaps and negative attitudes of the general public toward people living with HIV/AIDS have been identified and can be used to tailor educational campaigns in Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
41
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 17 publications
12
41
1
2
Order By: Relevance
“…The highest knowledge level was in the older age groups, in line with the findings of studies in India [14] and Saudi Arabia [10]. This can be attributed to more exposure to sexual health education, such as mandatory premarital trainings on sexual health and HIV, which are regularly practiced in Iran [11].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The highest knowledge level was in the older age groups, in line with the findings of studies in India [14] and Saudi Arabia [10]. This can be attributed to more exposure to sexual health education, such as mandatory premarital trainings on sexual health and HIV, which are regularly practiced in Iran [11].…”
Section: Discussionsupporting
confidence: 77%
“…The most common item for which participants reported an accepting attitude was related to taking care of an HIV-positive family member in one’s own home, which can be attributed to the family-oriented culture of Iran Similar results have been reported in Laos [15] and Saudi Arabia [10]. The lowest rate was related to the disclosure of a family member with HIV/AIDS, which reflects the fact that the stigma of HIV/AIDS is still a major issue in our community.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Recent studies in Malaysia (Wan et al, 2012;Mohd Saad et al, 2013;Munusamy and Fadzil, 2017), Nigeria and Democratic Republic of Congo (Gebremedhin et al, 2017); India (Hazarika, 2010); Zambia (Mutombo and Maina, 2015) Iran (Tafazoli et al, 2016) and Saudi Arabia (Alwafi et al, 2018) have revealed that women (including female sex workers) have generally low knowledge about HIV/AIDS but have positive attitudes towards HIV/AIDS. There are positive associations between levels of HIV/AIDS knowledge, attitudes, HIV risk perception and education level of which the higher a woman's education, the highest her levels of knowledge about, the perception of HIV/AIDS risk (in relation to condom use) and positive acceptance attitudes towards HIV/AIDS.…”
Section: Women's Knowledge Perceptions and Perceived Risk Of Hiv/aidsmentioning
confidence: 99%